(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To evaluate the outcomes of laparoscopic totally extraperitoneal repair for inguinal hernia at the center for on-demand medical services - Thai Nguyen national hospital, from August 2023 to August 2025. Subjects and methods: A descriptive cross-sectional study, combining retrospective and prospective data, was performed on 33 patients diagnosed with inguinal hernia and indicated for totally extraperitoneal repair. Results: The mean age of patients was 50.27 ± 16.177 years. Patients with normal BMI accounted for 87.9%. Right-sided hernias were present in 54.5% and left-sided in 39.4%. Indirect hernias represented 66.7%, while direct hernias represented 33.3%. The mean operative time was 89.55 ± 27.311 minutes. No intraoperative complications were recorded in 69.7% of cases, and 66.7% had no early postoperative complications. The mean time to mobilization was 1.21 ± 0.740 days, and the mean hospital stay was 3.45 ± 1.394 days. Good outcomes at discharge were observed in 97% of patients, and 87.9% maintained favorable results at follow-up. Conclusion: Laparoscopic totally extraperitoneal totally extraperitoneal repair is a safe and effective surgical technique for the management of inguinal hernia.